Formulation and Evaluation of Antimicrobial Activity of Marine Red Algae Gracilaria Corticata - Parthiban.R; Anbazhagan.S; Prakash.R (Asian Journal of Pharmaceutical Research and Development, 2025)
Objective: The present study was carried out to investigate the antimicrobial activity of formulated gel containing marine red algae Gracilaria Corticata belonging to the family Rhodophyta by disc diffusion assay method against bacterial and fungal organisms. Methods: The ethanolic extract of Gracilaria Corticatawere subjected to phytochemical and physiochemical analysis and then gel prepared using an ethanolic extract of Gracilariacorticata were divided into two different concentration such as 250 and 500 µg. The formulated gel was investigated for antimicrobial activity by disc diffusion assay method against S. aureus, P. aeruginosa, and Candida albicans and compared with standard drug ketoconazole (30µg) and amikacin (30µg). The zones of inhibition formed against organisms were calculated. Results: In the present study the formulated gel showed a moderately potent antimicrobial activity. The zone of inhibition of prepared gel against S. Aureus and P. aeruginosa was found to be 12 and 10 mm respectively. The zone of inhibition of prepared candida albicans was found to be 12 mm. And the phytochemical analysis shows the presence of active constituents such as flavonoids, sugar, phenol and quinones and physiochemical analysis shows that the antimicrobial activity is due to the presence of active constituents and evaluation of gel proves the stability of the formulation. Conclusion: The present study shows that the invitro anti-microbial activity of the formulated gel at the dose of 500 was higher inhibitory against virulent bacteria which cause various infection. From the above studies, it confirms the formulated gel exhibit moderately potent antimicrobial activity.